Pelayanan antenatal care dalam pengelolaan anemia berhubungan dengan kepatuhan ibu hamil minum tablet besi - Subarda Subarda; Mohammad Hakimi; Siti Helmyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: The prevalence of pregnant women with anemia is still one of nutrition problems in Indonesia. The main cause of this case is low iron supplementation compliance as the effect of lack of antenatal care (ANC) services and lack promotion of anemia prevention and iron tablet benefit.Objective: The study was aimed to know the relationship between ANC services in anemia management with iron supplementation compliance of pregnant women.Method: The study was observational with cross sectional design. Subjects were 202 pregnant women in the II–III trimester period in Asahan District. Sampling interpretation was randomly performed by choosing 3 sub-districts with K4 ≥ 85% and ≤ 85% coverage. Data collection was carried out by interview based on structured questionnaire and KIA literature study while validity of iron supplementation compliance using stool test. Data analyzed using chi-square and logistic regressions test.Results: The result showed that 41.1% of pregnant women were complied. Based on chi-square test, there were four significant variables related to pregnant women’s compliance namely ANC services (ratio prevalence 1.82; CI95%: 1.22-2.70), anemia assessment (ratio prevalence 1.79; CI95%: 1.22-2.64), nutrition consultation (ratio prevalence 1.41; CI95%: 1.12-1.76) and knowledge (ratio prevalence 1.42; CI95%: 1.12-1.79). Meanwhile logistic regressions test showed that the most influencing variable was ANC services (OR 3.125) after controlling knowledge variable.Conclusion: There were positive relationship between ANC services, anemia assessment, and nutrition consultation with iron supplementation compliance.